2022
DOI: 10.1021/acssensors.2c00685
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Discrimination of Benzene Series and Molecular Recognition of the Sensing Process over Ti-Doped Co3O4

Abstract: This work achieved the chemical discrimination of benzene series (toluene, xylene isomers, and ethylbenzene gases) based on the Ti-doped Co 3 O 4 sensor. Benzene series gases presented different gas-response features due to the differences in redox rate on the surface of the Ti-doped Co 3 O 4 sensor, which created an opportunity to discriminate benzene series via the algorithm analysis. Excellent groupings were obtained via the principal component analysis. High prediction accuracies were acquired via k-neares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 44 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The lengths of CO and H–O bonds on BSO-10 are 1.18 and 1.00 Å, respectively, which are 0.01 and 0.02 Å longer than those (1.17 and 0.98 Å) of BSO. The OCO bond angles of CO 2 decrease from 180.00 to 177.84° and 177.72° on the surface of BSO-10 and BSO, respectively, , which indicated that OVs had a slight effect on the adsorption and activation of CO 2 . Significantly, the adsorption energy of H 2 O molecules on BSO-10 was −0.85 eV, which was more negative than that of BSO (−0.77 eV).…”
Section: Resultsmentioning
confidence: 95%
“…The lengths of CO and H–O bonds on BSO-10 are 1.18 and 1.00 Å, respectively, which are 0.01 and 0.02 Å longer than those (1.17 and 0.98 Å) of BSO. The OCO bond angles of CO 2 decrease from 180.00 to 177.84° and 177.72° on the surface of BSO-10 and BSO, respectively, , which indicated that OVs had a slight effect on the adsorption and activation of CO 2 . Significantly, the adsorption energy of H 2 O molecules on BSO-10 was −0.85 eV, which was more negative than that of BSO (−0.77 eV).…”
Section: Resultsmentioning
confidence: 95%
“…21,22 For example, Dong et al conducted in situ DRIFTS to investigate the sensing reactions of toluene molecules over Mn-and Ti-doped Co 3 O 4 sensing materials. 23,24 Barsan et al employed in situ DRIFTS to study the sensing mechanisms of CO and H 2 molecules with NiO material while simultaneously measuring resistance. 25 In parallel, in situ Raman spectroscopy can track the structural evolutions of sensing material during gas sensing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, gas molecules and sensing materials could undergo structural changes when sensors are exposed to the targeted atmosphere. Monitoring the dynamic evolutions of gaseous molecules and sensing materials is essential to obtain comprehensive gas–solid interfacial interactions during gas sensing. In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) can probe the adsorbed species on the surface of sensing materials during gas sensing. , For example, Dong et al conducted in situ DRIFTS to investigate the sensing reactions of toluene molecules over Mn- and Ti-doped Co 3 O 4 sensing materials. , Barsan et al employed in situ DRIFTS to study the sensing mechanisms of CO and H 2 molecules with NiO material while simultaneously measuring resistance . In parallel, in situ Raman spectroscopy can track the structural evolutions of sensing material during gas sensing .…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–10 ] In addition, the surface catalytic reaction between active oxygen species and guest gases can significantly influence the selectivity and sensitivity of gas sensors. [ 11–13 ] Tailored nanostructure of sensitive material is beneficial for the adsorption/diffusion of gas molecules within the sensitive layer and exposing more abundant active sites for catalytic reaction. [ 14–16 ] Especially, mesoporous metal oxides make the gas molecules transport in the interconnected channels dominantly by Knudsen diffusion, which favors a fast mass transfer rate and the effective interaction of gas molecules with metal oxide grains.…”
Section: Introductionmentioning
confidence: 99%